Economically valuable traits, their level and correlations in the offspring of hybrid soybean populations - Biliavska, L. (Scientific Progress & Innovations, 2024)
The article presents the level of economically valuable traits and correlations in the offspring of different hybrid soybean populations. The development of varieties using soybean (Glycine max. (L.) Merr.) source material with high genetic yield potential and adaptive properties requires the use of modern breeding methods with an appropriate level of economically valuable traits. Modern methods of evaluation and selection of breeding samples make it possible to control economically valuable traits and their manifestation. The created F1 hybrids, as the initial forms of hybrid populations, differ in productivity and the yield structure elements that determine it. The breeding process is aimed at searching for heterotic forms by means of genetic determination of selectively significant traits and revealing their genotypic structure of variability.. The aim of our research was to determine the economically valuable traits and correlations between them in the offspring of hybrid soybean populations. Field experiments were conducted (2006–2019) in the experimental field of Poltava State Agrarian Academy. Soil was podzolised chernozem, predecessor was winter wheat. The research object was F1 hybrid combinations. The test varieties were Ametyst and Almaz, which are the most adapted to the Poltava region. Five varieties were studied, which, due to their high yields, have a more expressed value of the productivity components (number of beans, number of nodes, number of seeds, weight of 1000 seeds, weight of seeds per plant) – these are Ukrainian varieties: Ahat, Romantyka, Krasa Podillia, Altair and the Chinese variety Miao-yang-dou. In the offspring, plants with high values of economically valuable traits were identified, which were 2–5 times higher than the average population value (height of the lower bean, number of branches on the plant, weight of beans with seeds, weight of 1000 seeds, number of seeds per plant). They made up the selection group in the following generations. The correlations, their strength and direction between the traits that significantly affect plant productivity were revealed. The identified patterns made it possible to carry out targeted breeding to improve soybean plant productivity traits in the offspring of the intervarietal hybrids Ametyst/Krasa Podillia and Bravella/Bilosnezhka/Altair. Breeding groups were created on the basis of the best plants, which served as the source material for further breeding.